Promotional strategies towards incerasing the customer awareness in Kazzponic Sdn Bhd in Malacca / Khairil Imran Mohd Yahya - Mohd Yahya, Khairil Imran (Faculty of Business and Management, 2009)
In order to strengthen the local market for Kazzponic Sdn. Bhd. the important thing of marketing mix that come out from my survey is in terms of the promotional mix. This is because the promotion involves disseminating information about a product, product line, brand, or company. The promotional mix will not only help increase profit but also it will help to the development of company corporate image that will bear in the customer mind This is why the promotional mix on customer awareness is important to educate the customer on organic product is good in order to attract the potential customer to buy hydroponics product. Kazzponic need to give information on the benefit of using the hydroponics as more in order to attract more customers because this will help to increase the sales and profit of Kazzponic. Kazzponic Sdn Bhd basically focuses on hydroponics market and it also becomes the core product of this agriculture company. The observation by the researcher had found that the local market for Kazzponic Sdn. Bhd. is low in term of customer awareness. This is because the researcher had found that the company Kazzponic Sdn. Bhd. had exist for about 16 years which is 1993. The observation done by researcher is based on the passed promotion such as pamphlet, TV advertising and exhibition that Kazzponic Sdn. Bhd. had done.